2015
DOI: 10.3906/tar-1403-63
|View full text |Cite
|
Sign up to set email alerts
|

Solvent optimization and characterization of fatty acid profile and antimicrobial and antioxidant activities of Turkish Pistacia terebinthus L. extracts

Abstract: The present study investigated 12 different Pistacia terebinthus L. (terebinth) fruits, harvested or purchased in Turkey, for fatty acid composition, radical scavenging, antimicrobial activity, and total phenolic content. Solvent optimization for the samples was prepared by using a simplex lattice mixture design prior to the analysis. The optimum solvent mixture was 39% water and 61% acetone, based on the maximization of extraction yield of phenolic compounds. Total phenolic contents (TPCs) of the extracts var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 49 publications
1
9
1
1
Order By: Relevance
“…In the present study, distilled water was used for extraction, which allowed to obtain a high content of phenolic compounds in extracts that had high antioxidant potential, although water is not the most effective solvent. As many authors have shown earlier for vegetable raw materials, such as Pistacia terebinthus L. or Limnophila aromatica, methanol and acetone are much more effective solvents, allowing obtaining extracts with higher antioxidant potential and a higher concentration of bioactive compounds [24]. However, evaluation of the efficiency of water extraction allows us to determine, from the point of view of practical application, whether raw materials could be components of functional products in the future, i.e., infusions, beverages, smoothies or yogurts [25].…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, distilled water was used for extraction, which allowed to obtain a high content of phenolic compounds in extracts that had high antioxidant potential, although water is not the most effective solvent. As many authors have shown earlier for vegetable raw materials, such as Pistacia terebinthus L. or Limnophila aromatica, methanol and acetone are much more effective solvents, allowing obtaining extracts with higher antioxidant potential and a higher concentration of bioactive compounds [24]. However, evaluation of the efficiency of water extraction allows us to determine, from the point of view of practical application, whether raw materials could be components of functional products in the future, i.e., infusions, beverages, smoothies or yogurts [25].…”
Section: Discussionmentioning
confidence: 98%
“…The antiradical activity was determined by a method described by Durak and Ucak [31]. This method determines the free radical scavenging activity of pomegranate juice.…”
Section: Bioactive Propertiesmentioning
confidence: 99%
“…Hosseinzadeh et al, (2012) found similar results in studies showing the antioxidant activity on pistachio. However, in previous studies in different pistachio species that Polat (2016), Durak and Ucak (2015), Azadpour et al, (2015) and Rezai et al, (2015) reported different results from the study that antioxidant activity in the different parts in pistachio 31,42 to 90.96%, 64.4%, 21.1% and 23.02 % respectively.…”
Section: Resultsmentioning
confidence: 82%